PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA BERBASIS QUIZIZZ TERHADAP KETERAMPILAN MENYIMAK PESERTA DIDIK KELAS V SDN NO.15 INPRES ULUMANDA KABUPATEN MAJENE - Isra wati; Andi Adam; Desy Ayu Andhira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem in this study is whether there is a significant influence of the discovery learning model assisted by media based on quizizz on the listening skills of class V students of SDN No.15 Inpres Ulumanda, Ulumanda District, Majene Regency. This study aims to determine the effect of the discovery learning model assisted by media based on quizizz on the listening skills of class V students of SDN No.15 Inpres Ulumanda, Majene Regency in the Indonesian Language subject. This type of research is a quantitative research type with an experimental method and research design, namely one group pretest-posttest design, data is processed using SPSS version 25 windows, with a research sample of 15 class V students. Data collection techniques use pretest (initial test), implementation of treatment (treatment), posttest (final test) observation, and documentation. The data analysis technique used in this study is a descriptive analysis technique, and an inferential analysis technique, where the collected data is processed and analyzed using a normality test and hypothesis testing using a paired sample t-test. The results of this study indicate that there is an influence of the discovery learning model assisted by media based on quizizz on students' listening skills in the Indonesian Language subject, which can be seen from the descriptive data analysis of the pretest learning results of students getting a score of 67.73 while the posttest score of students getting a score of 91.73. Based on the hypothesis test using the paired sample t-test if the sig value <0.05 then there is an influence of variable x on variable y, and after the paired sample t-test was carried out, the results were 0.000 <0.05, which means there is an influence. Based on the results of the study above, it can be concluded that there is an influence of the discovery learning model assisted by media based on quizizz on the listening skills of class V students of SDN No.15 Inpres Ulumanda, Majene Regency in the Indonesian Language subject, there is a significant increase.